PROTECTIVE EFFECT OF CUMIN (CUMINUM CYMINUM L.) SEED EXTRACT ON CARDIOVASCULAR SYSTEM, TOXICITY, AND HEMATOLOGY ON HYPERLIPIDEMIC RABBITS: AN EXPERIMENTAL STUDY - Chouhan, Harshlata; Purohit, Ashok (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study is related with the assessment of anti-atherosclerotic efficacy of 70% EtOH extract of cumin seed in diet-induced hyperlipidemic rabbits. Methods: Rabbits were rendered hyperlipidemic by oral administration of cholesterol for 15 days. Then, the animals were treated with 70% EtOH (ethanolic extract) of cumin seed extract for 45 days (Group III). Another set of animals was treated with atorvastatin, the standard drug for 45 days. At the end of experimental period, the serum biochemical, hematological, and histological analysis of thoracic aorta was done. Results: The cumin seed extract showed contain hypolipidemic effect by reducing plasma cholesterol, low-density lipoproteins, and triglycerides level. While toxicological studies suggest no adverse effect on renal and liver function tests, hematological parameters were also observed in a normal range. Histological analysis showed that cholesterol administration caused a narrowing of the aortal lumen while treatment with 70% EtOH and atorvastatin decreased the plaque size and restored the luminal size of the aorta to normal. Conclusion: The present study suggests that commonly used culinary spice cumin seed possesses hypolipidemic and cardioprotective effect with a positive effect on serum biochemistry, histology, and hematology.